MODELING OF THE IMPORT SUBSTITUTION AND NATIONAL ECONOMY MODERNIZATION COMPLEX PROCESS WITH A MANAGEMENT THROUGH THE NATURAL MONOPOLIES OF THE COUNTRY - M. Kuternin (Вестник университета, 2017)
In the article, it is shown that the present stage most important problem of economic development of Russia can be formulated as a complex problem of import substitution and modernization of the economy. The plan of transition to the new technological way based on use of the domestic and available import equipment is developed by means of mathematical modeling. In the article, it is shown that natural monopolies of the country can be an effective tool of indirect state regulation at the solution of a complex task of import substitution and modernization of the economy.